Prenatal Risk Factors of Autism Spectrum Disorder Compared to Congenital Visual and Hearing Loss: A Case-Control Study - Mansournia, Mohammad Ali; Nakhostin-Ansari, Amin; Shayestehfar, Monir; Memari, Amir Hossein (Iranian Journal of Child Neurology, 2025)
Objectives: Relations exist between autism spectrum disorder (ASD) and visual and hearing loss (VL/HL). This study evaluated the prenatal risk factors specific to ASD compared to VL/HL. Materials & Methods: This case-control study recruited individuals with ASD to compare with individuals with VL/HL as controls from special schools. Parents completed a questionnaire containing questions about demographic characteristics, socioeconomic status, family history of neurological or psychological disorders, and problems during the pregnancy. Results: Five hundred thirty-six participants were enrolled in the study, of which 238 (44.4%) had ASD, 198 individuals had HL (36.9%), and 100 had VL (18.7%). Seven (2.9%) participants in the ASD group were male, significantly (p<0.001) lower than the proportion of males in the HL/VL group (99, 33.2%). In the final regression model, higher educational levels of parents and gestational hypertension were associated with a higher risk of ASD (p<0.05). However, female gender, parents not living together, and cousin marriage were associated with a higher risk of HL/VL (p<0.05). Conclusion: This preliminary study determined the factors more associated with ASD than HL/VL. Believably, the study’s results could shed more light on the exclusive risk factors of ASD